Quantitative ethnobotanical analysis of ethnomedicinal flora used by the Eastern Himalayan Indigenous Communities of Assam, India - Begum, Kajoli; Mylliemngap, Wishfully; Nicolee Lyngdoh (Ethnobotany Research and Applications, 2024)
Background: For generations, indigenous communities have used plants as ethnomedicinal remedies, offering affordable treatments where modern medicine is scarce, especially in remote areas. However, this knowledge is eroding due to dwindling belief and interest among future generations, and lack of comprehensive documentation. This review aims to document the ethnomedicinal use of therapeutic flora by indigenous communities in Assam’s hilly districts through a critical examination of selected literature. Investigating the ethnobotanical expertise of these tribes may unveil insights for novel pharmaceuticals and preserving these crucial traditional practices. Methods: A total of 12 research papers published from 2004 to 2020 were analyzed to study the use of ethnomedicinal plants by tribal communities in Dima Hasao and Karbi Anglong districts of Assam. Data analysis involved Family Use Value (FUV), Use Value of species (UV), Informant Consensus Factor (FIC), Fidelity Level (FL) and plant part used (%) using Microsoft Excel 2013. Results: The findings revealed the utilization of 273 species of ethnomedicinal plants from 208 genera and 83 families, addressing 10 broad disease categories and 91 specific types of ailments. The majority of remedies consisted of plant leaves (35%) with Morinda angustifolia Roxb. being the most commonly prescribed species by local herbalists (UV=5.00). Conclusions: The study highlighted that tribal communities hold extensive knowledge and reliance on traditional medicine despite modern healthcare advancements. Plants exhibiting higher UVs, UVf, FL and FIC are crucial for conservation prioritization. This documented knowledge can guide further research potentially leading to discovering bioactive compounds for modern medicines. Keywords: Dima Hasao, Karbi Anglong, Ethnomedicinal plants, Indigenous Communities, Diseases.